The human dilemma of displacement Towards a practical theology and ecclesiology of home - Brunsdon, Alfred (AOSIS, 2020)
In this book social responsive theological research converges to provide practical theological and ecclesiological perspectives on the growing human dilemma of displacement. The book presents the research of practical theologians, a missiologist and a religious practitioner whose work pertains first and foremost to the (South) African context. The different fields of expertise of the contributors within the broader field of practical theology worked towards a unique compilation of themes, each relevant to the issue at stake. The majority of chapters are theoretically orientated, except where authors refer to empirical work conducted during previous research. The main contribution of this collaborative work is to be sought in the practical theological and ecclesiological perspectives it provides. It engages the critical questions of what kind of church we need, and what kind of care we should provide in the face of the growing predicament of human displacement. The theological and theoretical principles uncovered in the different chapters will be of use to theologians from all theological subdisciplines, as well as to religious practitioners and leaders of faith communities that are challenged with the growing realities of strangers on their doorsteps and in their pews.